Analysis of Basic Students Learning Difficulties in Multiple Materials - Silvy Yulistia Salsabila; Geri Syahril Sidik; Rizki Hadiwijaya Zulkarnaen (Universitas Sebelas Maret, 2021)
This study aims to obtain an overview of learning difficulties. This research was conducted in third class of SDN 2 Cintaraja. The research method used is descriptive qualitative. The data collection technique was carried out in two ways, namely by giving story questions and interviews. The story questions used in this study were three questions which refer to four characteristics of student learning difficulties according to Jamaris in 2014 (weakness in counting, difficulty in transferring knowledge, understanding of mathematical language, difficulty in visual operations) regarding the multiplication. The results showed that there were still many students who had learning difficulties in this multiplication material, of the six students who were sampled all of them were only able to master one characteristic of the four characteristics of learning difficulties, namely in terms of understanding the language of mathematics, while the other three learning difficulties had not able to be mastered by them, namely in terms of calculating weaknesses, difficulties in transferring data, and difficulties in visual operations of the multiplication material.